FANATISME DALAM BERORGANISASI (Studi Sikap Pengurus Pimpinan Daerah Muhammadiyah Ponorogo) - Wahyudi Setiawan (Universitas Muhammadiyah Ponorogo, 2014)
Fanatism is an unseparated part of Moslem mass organisation as long running their mission of puton. Totality in doing puton always been done by the activist to reach a goal based on their intention and want. This of course, happens based on the moral valve that insist or their Moslem organisation that they choosen, shich oftenly appear a fanatism inside of the Moslem activist during their puton. So, sometimes the society outside the mass organitation, feel uncomfortable sith the existence of that Moslem organization. This research is written to know/find out somethings about fanatism that exist in Moslem organization. By understanding the meaning and causes of fanatism and their way of thinking. This research is expected to give much contribution not only to the Moslem organization activist, but also to the Moslem generally. In qualitative research, it is really exact to know many problems above. The data will be submitted by doing private interview and observation. Then by interpreting the written dare and continved by doing analysist of the results is as follow: 1). Fanatism is been understood in two meaning; a). Positive fanatism, a fanatism attivade that appear because of the conscious and somebody?s understanding in the main problem or object; b). Negative fanatism, a fanatism attitude that appears because of the importance in every case without understanding the main problem clearly. 2). The religious commitment of an activist is based on their own and their mahdah relations, while their ghoiru mahdah is definite good. 3). To the activist Moslem organization become a part of puton that exits. The media that used in puton take a point of view based on the problems that be up afainst and they are truly wise in tolerating the difference among Moslem organization by up holding the valve of tolerance it self.